2013
DOI: 10.2337/db12-0789
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Based Screening Identifies Paroxetine as an Inhibitor of Diabetic Endothelial Dysfunction

Abstract: We have conducted a phenotypic screening in endothelial cells exposed to elevated extracellular glucose (an in vitro model of hyperglycemia) to identify compounds that prevent hyperglycemia-induced reactive oxygen species (ROS) formation without adversely affecting cell viability. From a focused library of >6,000 clinically used drug-like and pharmacologically active compounds, several classes of active compounds emerged, with a confirmed hit rate of <0.5%. Follow-up studies focused on paroxetine, a clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 33 publications
3
70
0
Order By: Relevance
“…Data of the present investigation showed that paroxetine didn't significantly alter the blood glucose level. This finding is in accordance with that of Gerö et al [51]. Results of the present study showed that paroxetine moderately decreased the gene expression of the enzyme GSK-3b in the hippocampal tissues as proved by RT-qPCR test, a result which reflects a decrease in the level and/or activity of the enzyme.…”
Section: Discussionsupporting
confidence: 94%
“…Data of the present investigation showed that paroxetine didn't significantly alter the blood glucose level. This finding is in accordance with that of Gerö et al [51]. Results of the present study showed that paroxetine moderately decreased the gene expression of the enzyme GSK-3b in the hippocampal tissues as proved by RT-qPCR test, a result which reflects a decrease in the level and/or activity of the enzyme.…”
Section: Discussionsupporting
confidence: 94%
“…The MTT method was performed as described [28]. Briefly, 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) was added to the cells at a final concentration of 0.5 mg/ml and cells were cultured at 37 °C for 1 hour.…”
Section: Methodsmentioning
confidence: 99%
“…U937 cells were incubated with MitoSox Red (5 mM; Life Technologies, Grand Island, NY) 10 minutes at 37°C in dark or with 29,79-dichlorofluorescein (5 mM; 29,79-dichlorofluorescein H 2 DCF) 30 minutes at 37°C before hydrogen peroxide (H 2 O 2 ) challenge. Fluorescence signal was measured as described (Gerö et al, 2013b) on Synergy 2 (Ex/Em of MitoSox Red: 510/580 nm; Ex/Em of reactive oxygen species detection reagent: 490/520 nm) (BioTek, Winooski, VT).…”
Section: Introductionmentioning
confidence: 99%